Cadmium fractionation in soils affected by organic matter application: Transfer of cadmium to cacao (Theobroma cacao L.) tissues - Gutiérrez, Eduardo; Chávez, Eduardo; Gamage, Kasuni H. H.; Argüello, David; Galkaduwa, Madhubhashini B.; Hettiarachchi, Ganga M. (Frontiers in Environmental Science, 2022)
Elevated cadmium (Cd) concentrations in cacao (Theobroma cacao L.) beans have concerned chocolate consumers worldwide because of the potential detrimental human health effects. Compost application on the soil surface could modify the labile Cd in soils and yet it could enhance Cd bound to humic and fulvic acids, forming an organo-metallic complex that could reduce the availability of Cd to plants. This study investigated the effect of surface compost applications at two rates, the chemistry and fractionation of Cd at two soil depths, and the relationship of these soil Cd pools with plant uptake. The research was carried out on four Ecuadorian cacao farms. The compost was applied at 6.25 Mg·ha−1 (low) and 12.5 Mg·ha−1 (high) per annum. There was also a control treatment with no compost application. Soil samples were collected at two depths, surface (0–5 cm) and below surface (5–20 cm). Leaf samples and cacao pots were collected from each treatment. Soil Cd was fractionated into five operational pools. Additionally, the Cd-bound to fulvic acids and humic acids in soils were extracted separately. The EDTA-extractable fraction showed the highest concentration of Cd at both depths. Cadmium bound to fulvic acids was higher in compost-applied soils than in the control (p < 0.05) in all farms. Leaf and bean-Cd were negative and significantly correlated with the Cd extracted by EDTA, NaOH, HNO3, and FA-Cd pools. The mobility of Cd in soils cultivated with cacao, based on plant uptake, was strongly associated with the soils’ chemical characteristics, especially pH and SOC. The surface application of organic matter facilitates the redistribution of Cd in soil fractions, mainly in EDTA-, NaOH-, and HNO3-extractable fractions, suggesting a reduction in Cd soil–plant transfer via adsorption or complexation processes. Apparently, the application of high-quality compost, i.e., high FA content, could aid in mitigating Cd contamination in cacao orchards. Experiments on perennial crops merit a longer evaluation time to better assess the changes in plant-Cd.